EXPLORATIVE STUDY ON THE PHENOMENON OF CONTRABAND CIGARETTES IN NORTHERN MALAYSIA - Vijayan, Kamalahasan; Chethiyar, Saralah Devi Mariamdaran (PEOPLE: International Journal of Social Sciences, 2020)
Contraband or smuggled cigarettes have caused socio-economy devastation and loss of revenue for this country. These cigarettes are sold at a lower price compared to the original cigarettes thus; attention is shifted to obtain the cheaper product. Law and law enforcement actions have been well defined; thus, such a phenomenon continues to occur. This study aims to explore the phenomenon of cigarette smuggling in Northern Malaysia and establish that attention is required to unearth the contributing factors and implement effective measures. This study was conducted using library design with reference materials derived from various resources related to the study. Based on the study conducted, contraband cigarettes impose a negative impact on the country, and identifying the contributing factors and combating this phenomenon is imperative. Combating this phenomenon requires close collaboration between the public, traders, and government.